Berberine Ameliorates High Glucose-Induced Cardiomyocyte Injury via AMPK Signaling Activation to Stimulate Mitochondrial Biogenesis and Restore Autophagic Flux - Hang, Weijian; He, Benhong; Chen, Jiehui; Xia, Liangtao; Wen, Bing; Liang, Tao; Wang, Xu; Zhang, Qianying; Wu, Yue; Chen, Qingjie; Chen, Juan (Frontiers in Pharmacology, 2018)
Background Type II diabetes (T2D) induced cardiomyocyte hypertrophy is closely linked to the impairment of mitochondrial function. Berberine has been shown to promising effect for hypoglycemia in type II diabetes models. High Glucose induced cardiomyocyte hypertrophy in vitro has been reported. The present study investigated the protective effect and the underlying mechanism of berberine on high glucose-induced H9C2 cell line. Methods High glucose-induced H9C2 cell line was used to mimic the hyperglycemia resulting in cardiomyocyte hypertrophy. Berberine was used to rescue in this model and explore the mechanism in it. Confocal microscopy, Immunofluorescence, RT-PCR and western blot analysis was performed to evaluate the protective effects of berberine in high glucose-induced H9C2 cell line. Results Berberine dramatically alleviated hypertrophy of H9C2 cell line and significantly ameliorated mitochondrial function by rectified the imbalance of fusion and fission in mitochondrial dynamic. Furthermore, berberine further promoted mitogenesis and cleared the damaged mitochondria via mitophagy. In addition, berberine also restored autophagic flux in high glucose-induced cardiomyocyte injury via AMPK signaling pathway activation. Conclusion Berberine ameliorates high glucose-induced cardiomyocyte injury via AMPK signaling pathway activation to stimulate mitochondrial biogenesis and restore autophagic flux in H9C2 cell line.